Effects of explaining system failures during maneuver coordination while driving manual or automated. (December 2020) - Kraft, Ann-Kathrin; Maag, Christian; Cruz, Maria Isabel; Baumann, Martin; Neukum, Alexandra
Highlights: System failures during maneuver coordination are evaluated. The effect of an explanation of the system failure is investigated. The results revealed decreased trust in the system after a failure for short time. The explanations were perceived as helpful, but no effect on acceptance was found. Abstract: To support the coordination of road users in situations like merging or turning left, an advanced driver assistance system for cooperative driving could be helpful whether driving manually or automated. This simulator study investigated the behavior of drivers being confronted with system failures. In two test situations with system failures (loss of communication of the system and change of traffic environment), the system could not complete the coordination properly and the driver was informed about the system failure and the abortion of maneuver coordination. The focus of this study was to analyze the effect of system failures on drivers' trust in the system and whether an explanatory message provided by the system would increase acceptance. Therefore, subjective data as well as gaze and physiological data of 32 participants were analyzed. The results revealed decreased trust in the system after experiencing a system failure, but no long term effect was found. The drivers evaluated the timing, as well as the content, of the explanatory message as appropriate. The explanations were perceived as helpful, but no effect on acceptance was found.